The excellent spontaneous ultraviolet emission of GaN nanostructures grown on silicon substrates by thermal vapor deposition. (January 2015) - Saron, K.M.A.; Hashim, M.R.; Qaeed, M.A.; Al-heuseen, K.; Elfadill, Nezar G.
Abstract: In this study, GaN nanostructures were grown on p-Si (111) substrate by thermal chemical vapor deposition (TCVD). Ga vapor directly reacted with NH3 solution in N2 carrier gas flow of 2 L/min at different temperatures (950–1050 °C). The influence of NH3 solution and growth temperature on the morphology, structure, optical and photoresponse properties of GaN nanostructures was investigated. Scanning electron microscopy images showed that the densities of the NWs varied with increasing temperature. The use of NH3 solution and increased growth temperature improved the crystalline quality of GaN nanostructures. The photoluminescence (PL) spectra of nanostructures displayed a near band-edge (NBE) emission at around 363–367 nm. Higher growth temperature (1050 °C) resulted in a strong NBE emission with no yellow emission peak. With +5 V applied bias, the NWs metal–semiconductor–metal UV photodetector exhibited a high photocurrent of 1.6×10 −3  A. The photocurrent to dark current contrast ratio was 120.